The “Seal of the Living God” in Rev 7:1-8: An Exegetical Study - Agustin, Jr., Alfredo G. (11th International Scholars Conference, 2017)
This study deals with the meaning of the “Seal of the Living God” in Rev 7:1-8. Several scholars interpret this seal as Baptism, while others suggest that this is the Holy Spirit. Others say, it is the name of God and the Lamb and is simply a seal of ownership and protection. Only very few biblical scholars have written an in-depth study on this issue. A dissertation has been published on this issue. The author suggests that the “seal” is the names of God and the Lamb. He also insists that the “acts of sealing” is externally manifested through Christo-theological confession that clearly identifies the true Jews from all nations. However, the author does not see Rev 7 and 14 in the context of obedience or disobedience to God’s commandments in the end-time issue of worship in decoding the meaning of the “seal of the living God.” The author of an article dealing with the “Mark of the Beast as a ‘Sign Commandment’ and ‘Anti- Sabbath’ in the Worship Crisis of Revelation 12-14” identified the mark of the beast as a direct parody of the Sabbath. Consequently, he suggested that the Sabbath is the eschatological sign and seal of covenant loyalty to the God of creation and redemption. However, this author failed to deal with the relation of Rev 7 and Rev 14 in decoding the meaning of the “seal of the living God.” The present study focuses on the meaning of the “seal of the living God” of Rev 7:1-8, which may also link it with Rev 14. The historical-grammatical method was employed in this exegetical study.